The applicability of weather derivative usage on tobacco farming in Zimbabwe (1991-2017). - Mabweazara, Nyasha (Midlands State University, 2018)
Financial derivatives are used for hedging and transferring of risks in the financial system, government planning and regulatory systems. Derivatives have been used as a tool to identify risks and develop strategies to address the risks in Agriculture. The study’s main aim is to investigate the applicability of weather derivatives on tobacco farming in Zimbabwe and examines its role in production. Thus by studying the issue within the context of Zimbabwe weather patterns and their relation to tobacco prices, the central null hypothesis to be addressed: Weather derivatives are not applicable in tobacco farming in Zimbabwe. The hypothesis was formulated to gain a better understanding of weather derivatives feasibility in tobacco farming. Thus, annual data of rainfall patterns, temperature and prices of tobacco for the period 1991 to 2017 was analysed. Time series for annual data was used as the source of data. The Ordinary Least Squares (OLS) was used in the analysis of the econometric model to determine the casual relationship between weather related events and tobacco prices. The study seeks to examine the need to improve regulatory policies in application of the weather derivatives in tobacco farming. The results indicate the need for weather derivatives use in tobacco farming given the fact that preconditions that are conducive for their adoption are satisfied. This include key dimensions namely; financial literacy by agricultural bodies; i.e. Tobacco research board, Tobacco Industry and Marketing Board (TIMB), farmers and government regulators. Given that most of the preconditions were not satisfied, the study does not reject the null hypothesis concluding that weather derivatives are not applicable in Zimbabwe, at the current moment. The study suggested recommendations to financial institutions, farmers and government to develop a framework to adopt weather derivatives as an alternative source of finance and implementing fiscal policies as well as to hedge weather related risks in tobacco farming.